Faktor-Faktor Yang Menpengaruhi Hasil Belajar Mata Kuliah Alat Berat Dan Pemindahan Tanah Mekanis Program Studi Pendidikan Teknik Bangunan FT UNP - Mega Kurniawati; Mahdika Putra Nanda; An Arizal (Jurnal Ilmiah Kanderang Tingang, 2023)
Learning is a process of interaction between the delivery of the message to the recipient via the media messenger. Lessons take place effectively and efficiently will result in maximum learning results. Factors that affect learning outcomes are individual factors include the physical and spiritual conditions of students, and students of environmental conditions around, social and non-social, as well as the factor of learning approach. Factor approach to learning was an attempt by both teachers and students that includes strategies and methods in the learning process. Based on the observation of the learning process at SMK 5 of Padang found more teachers dominate the classroom, so that active students in the classroom is not visible. Low student learning outcomes SMK 5 of Padang caused by various factors. One of these students are less actively involved in the learning process. Statics studies more are understanding the concepts and formulas, requires an understanding of older students with exercises that much. By using the expository method, the dominance of teachers more reduced. Guided Note Taking is studies active students who can assist in the learning process so that students can be independent in understanding and being able to build his own knowledge. This study aims to determine differences in the results of class X student TGB1-A SMK 5 of Padang after the application of the expository method using Guided Note Taking a class X TKB-A which uses conventional learning. This research uses research Quasi-Experimental (quasi-experiment). This type of research design Pretest-Posttest Control Group Design. Pre-test conducted before implementing learning to know the students' prior knowledge. After application of the expository method using a guided note taking increased learning outcomes in the experimental group compared with the control group.